High Sensitivity Polymer Visible‐Near Infrared Photodetectors via an Inverted Device Structure and Manipulation of Injection Barrier Height. Issue 25 (20th June 2016) - Wu, Siping; Xiao, Biao; Zhao, Baofeng; He, Zhicai; Wu, Hongbin; Cao, Yong
Abstract : Visible‐near infrared photodetectors are reported with excellent overall device parameters from conjugated polymers with different optical bandgaps by optimal design in device structure and optimizing the thickness of the photoactive layer in nanoscale. The best visible‐near infrared photodetectors show high detectivity ( D *) of 1.7 × 10 13 Jones at a wavelength of 710 nm, which is among one of the best results of polymer photodetectors reported to date.